Comparison of Micro-Osteoperforation and Platelet-Rich Fibrin Methods in Accelerated Orthodontic Tooth Movement - Tyszkowski, Monika (Archive of Orofacial Data Science, 2024)
AIM: The purpose of this thesis was to compare two methods of accelerated orthodontic tooth movement (OTM) in adults: Micro-osteoperforation (MOP) and platelet-rich fibrin (PRP/PRF) regarding the speed of canine retraction and other teeth OTM in terms of patient comfort measures. METHODS: From over 3000 searches in different sources like PubMed, Cochrane Library, and Google Scholar, 21 peer-reviewed articles from 2015 to 2022 were selected. All the studies researched healthy, non-growing humans aged 16-40, diagnosed with Class II div 1 malocclusion with first premolar extraction or molar distalization or incisors crowding. RESULTS: Both methods accelerated orthodontic tooth movement. The MOP method was slightly faster than the PRP/PRF method but more painful. There were a few reported side effects including root resorption, anchorage loss, and canine tipping more in the MOP studies. More MOPs placed less often were more effective. Higher platelet concentration injected more often had a better result. Both methods had inflammatory markers, particularly IL-beta elevated in the gingival crevicular fluid, which persisted longer in the MOPs. Gingival and plaque indexes showed clinically insignificant differences in MOP trials and were not measured in PRP/PRF studies. CONCLUSION: Both experimented accelerated OTM methods can help to shorten adult treatment comfortably. Nevertheless, further studies on the PRP/PRF method, are needed.